Trajectories of family disadvantage in the Longitudinal Study of Australian Children. - Shipley, M; Blakemore, T; Zubrick, S (My University, 2010)
Families, by virtue of the resources they have access to and/or control over, may be a source of both resilience and risk for children. When the resources available to children are limited, they may be disadvantaged, at risk of poor outcomes and vulnerable to social exclusion. This paper builds on previous work that established an index of multiple disadvantage for families participating in the Longitudinal Study of Australian Children (LSAC). The index includes measures of family socio-economic circumstances, indicators of health and wellbeing and perceptions of support and safety. We use Waves 1 to 3 of LSAC to examine the transition of young Australian families into and out of multiple disadvantages. This paper exploits the longitudinal nature of LSAC to explore and describe the trajectories of families with multiple disadvantages and the implications for their use of health and community services. Families experiencing multiple disadvantages can face challenges in providing the developmental resources necessary for positive outcomes. Meeting the complex needs of families who experience multiple and entrenched problems poses a distinct challenge to social policy-makers and service providers. Understanding families' transitions in and out of multiple disadvantages provides vital information for social inclusion policy and program interventions.
Keywords: Disadvantage; Disadvantage, adversity and resilience; Disadvantage; Adversity and resilience; Dsiadvantage, adversity and resilience